Maintenance Analysis of Sterilizer Machine Treatment at PT. Karya Tanah Subur (KTS) Using the Overall Equipment Effectiveness (OEE) Method - Ahmad Rizal; T.M Azis Pandria (Jurnal Inotera, 2023)
PT. Karya Tanah Subur (KTS) is a company engaged in the oil palm plantation and processing business located in Padang Sikabu Village, Kaway XVI sub-district, Aceh Barat Regency. The resulting production is crude palm oil CPO (Crude Palm Oil) or crude palm oil Palm Kernel (PK) and shells. In processing crude palm oil, the Boiling Station (sterilizer) is one of the most important machines, because if the sterillizer machine is damaged it will affect the production process of the factory. The purpose of this study was to analyze the performance of the sterilizer using the Overall Equipment Effectiveness (OEE) method by calculating the average Avaibility, Performance Efficiency, Rate Of Quality, and OEE values ​​from the performance of the sterilizer so that maintenance actions can be determined. Based on the analysis results, the average Availability is around 58.44%, Performance Efficiency is 80.77%, Rate Of Quality is 100% and the average OEE value on the Sterillizer machine is 46.43%, with these values ​​when compared to the international standards then it will be a fairly high difference..